Hearts and Minds: The Rise of Romanticism in Literature - Zahro Qodirova Zafarovna (Peerian Journals Publishing, 2025)
This article explores the origins and evolution of Romanticism, a literary and artistic movement that emerged as a reaction to the industrial revolution and growing utilitarianism. It emphasizes the Romantic celebration of nature, emotion, and individual experience, contrasting sharply with the rationalism of the time. The piece highlights key male and female contributors, such as William Blake, Mary Shelley, and Jane Austen, noting the rise of female writers and the growing popularity of the novel and Gothic fiction. Ultimately, Romanticism is portrayed as a powerful countercultural movement that sought beauty in both light and darkness.
Keywords: Romanticism; emotion; nature